Association of maternal KIR gene content polymorphisms with reduction in perinatal transmission of HIV-1 - Omosun, Yusuf O. (PLoS One, 2018)
The role of killer cell immunoglobulin-like receptors (KIRs) in the transmission of HIV-1 has not been extensively studied. Here, we investigated the association of KIR gene content polymorphisms with perinatal HIV-1 transmission. The KIR gene family comprising 16 genes was genotyped in 313 HIV-1 positive Kenyan mothers paired with their infants. Gene content polymorphisms were presented as presence of individual KIR genes, haplotypes, genotypes and KIR gene concordance. The genetic data were analyzed for associations with perinatal transmission of HIV. There was no association of infant KIR genes with perinatal HIV-1 transmission. After adjustment for gravidity, viral load, and CD4 cell count, there was evidence of an association between reduction in perinatal HIV-1 transmission and the maternal individual KIR genes KIR2DL2 (adjusted OR = 0.50; 95% CI: 0.24–1.02, P = 0.06), KIR2DL5 (adjusted OR = 0.47; 95% CI: 0.23–0.95, P = 0.04) and KIR2DS5 (adjusted OR = 0.39; 95% CI: 0.18–0.80, P = 0.01). Furthermore, these maternal KIR genes were only significantly associated with reduction in perinatal HIV transmission in women with CD4 cell count ≥ 350 cells/ μl and viral load <10000 copies/ml. Concordance analysis showed that when both mother and child had KIR2DS2, there was less likelihood of perinatal HIV-1 transmission (adjusted OR = 0.44; 95% CI: 0.20–0.96, P = 0.039). In conclusion, the maternal KIR genes KIR2DL2, KIR2DL5, KIR2DS5, and KIR2DS2 were associated with reduction of HIV-1 transmission from mother to child. Furthermore, maternal immune status is an important factor in the association of KIR with perinatal HIV transmission.